Pyramidal Business Groups and Asymmetric Financial Frictions - Duksang Cho (KDI Journal of Economic Policy, 2019)
Given capital market imperfections, an entrepreneur can alleviate financial frictions by creating a pyramidal business group in which a parent firm offers its subsidiary firm internal finance. This endogenous creation of pyramidal business groups can beget asymmetric financial frictions between business-group firms and stand-alone firms. I build a model to show that these asymmetric financial frictions can have sizable effects on resource allocation. On one hand, the financial advantage of pyramidal business groups can foster productive firms by incorporating them as subsidiaries. On the other hand, the asymmetrically large amount of external capital controlled by pyramidal business groups can be expended by unproductive business-group firms and push up the equilibrium price of capital. The model suggests that with fine investor protection or low financial frictions, the benefits of pyramidal business groups can be dominated by their costs because the probability of fostering productive subsidiaries diminishes as the efficiency of external capital markets improves, while the prevalence of pyramidal business groups is not attenuated due to their continuing asymmetric financial advantage.
Keywords: E23; E44; G32; O16; 330; Business Group; Capital Market; Financial friction; Pyramidal Ownership Structure; Resource Allocation